Learning sports initiation through CLIL dissemination - González-Fernández , Francisco Tomás; Fernández-Barrionuevo , Eliseo; Arce-Romeral , Lorena; Baena-Extremera , Antonio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to teach students how to communicate and disseminate an idea linked to learning of sport education. Fifty-two students of Sport Science from a Pontifical University of Comillas, participated in a congress of sports sciences. The present work is based on learning of sport education and in a complementary way, it will improve learning of foreign languages through the CLIL methodology (content and language integrated learning). In this way, the use of new technologies must be added as a tool for research, communication and dissemination so required and used today in education, since our project aims to build meaningful learning, achieving a meta-learning that favors educational success. The results obtained suggest that the realization of this professional practice helped the students to create elaborate ideas, try to identify problems encountered by seeking plausible solutions, and build a personal autonomy that will help them to create knowledge.